(untitled) (Scientific journal of the Fergana State University, 2024)
In this work, perovskite material with bright green quantum dots CsPbBr3 was synthesized using the ligand-assisted reprecipitation (LARP) method. Stability and spectral analysis of CsPbBr3 perovskite in different antisolvents were studied. During the synthesis, it was found that the substances used as ligands affect the particle size during the formation of quantum dots. It was found that the formation of CsPbBr3 perovskite quantum dots in the bright green or blue region depends on the concentration of the precursor, the nature of the antisolvent, and the structure of the ligands. The relationship between the stability and spectra of the perovskite compound containing CsPbBr3 was analyzed. Synthesized perovskite structured materials can be used for semiconductors, LED lamps, photocatalytic processes and solar cells.